2012
DOI: 10.1111/j.1467-8624.2012.01760.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depressive Symptoms, Dysfunctional Cognitions, and Infant Night Waking: The Role of Maternal Nighttime Behavior

Abstract: Mechanisms were examined to clarify relations between maternal depressive symptoms, dysfunctional cognitions, and infant night waking among 45 infants (1-24 months) and their mothers. A mother-driven mediational model was tested in which maternal depressive symptoms and dysfunctional cognitions about infant sleep predicted infant night waking via their impact on mothers' bedtime and nighttime behavior with infants (from video). Two infant-driven mediational models were also examined, in which infant night waki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(125 citation statements)
references
References 41 publications
7
100
1
1
Order By: Relevance
“…These findings support and extend earlier work (Teti, Crosby, McDaniel, Shimizu, & Whitesell, 2015), who reported that maritally distressed mothers who co-slept with their infants at 1 month were more likely to maintain these co-sleeping arrangements through 6 months, compared to non-distressed co-sleeping mothers at 1 month, who by contrast were more likely to move their infants into solitary sleep by 6 months. The present findings also extend the findings of Teti and Crosby (2012), who found that mothers with elevated depressive symptoms and excessive worries about their infants’ nighttime sleep behavior were more likely to seek out and spend time with their infants during the night than mothers with low symptom levels, and that this propensity for doing so was largely unrelated to whether or not their infants were distressed.…”
Section: Discussionsupporting
confidence: 87%
“…These findings support and extend earlier work (Teti, Crosby, McDaniel, Shimizu, & Whitesell, 2015), who reported that maritally distressed mothers who co-slept with their infants at 1 month were more likely to maintain these co-sleeping arrangements through 6 months, compared to non-distressed co-sleeping mothers at 1 month, who by contrast were more likely to move their infants into solitary sleep by 6 months. The present findings also extend the findings of Teti and Crosby (2012), who found that mothers with elevated depressive symptoms and excessive worries about their infants’ nighttime sleep behavior were more likely to seek out and spend time with their infants during the night than mothers with low symptom levels, and that this propensity for doing so was largely unrelated to whether or not their infants were distressed.…”
Section: Discussionsupporting
confidence: 87%
“…Additional methods for assessment, such as in-home visits and unobtrusive observation of the infant sleep environment have been suggested [21]. Some researchers have also utilized video-recordings throughout the night in the home to document infant sleep practices [46][47][48][49][50][51]. In addition, for most of the studies, the data collection tool was newly created for the purposes of that study.…”
Section: Evaluation Design/study Methodsmentioning
confidence: 99%
“…However, the nature of the association between attachment and sleep problems, if it can be shown to be reliable, may be complex and may involve a number of factors also known to be implicated in the connection between childhood psychopathology and sleep. For instance, Teti and Crosby tested a model in which maternal presence during the night (defined as the presence of the mother in the same room or close physical contact) acted as a mediator between maternal depression and child awakenings (Teti & Crosby, 2012). In that study, the association between maternal depressive symptoms and child awakenings was no longer statistically significant after controlling for maternal presence with the infant during the night.…”
Section: Disorganized Attachment Sleep and Developmentmentioning
confidence: 97%